Adolescent endometriosis. (February 2017) - Sarıdoğan, Ertan
Abstract: Endometriosis is a common finding in adolescents who have a history of chronic pelvic pain or dysmenorrhoea resistant to medical treatment, however the exact prevalence is unknown. Both early/superficial and advanced forms of endometriosis are found in adolescents, including ovarian endometriomas and deep endometriotic lesions. Whilst spontaneous resolution is possible, recent reports suggest that adolescent endometriosis can be a progressive condition, at least in a significant proportion of cases. It is also claimed that deep endometriosis has its roots in adolescence. Optimum treatment is far from clear and long term recurrence is still a significant problem. The most frequently reported treatment approach in the published literature is a combination of surgery and postoperative hormonal treatment with the combined oral contraceptives, progestins, levonorgestrel intrauterine system or gonadotrophin releasing hormone analogues. Use of gonadotrophin releasing hormone analogues and long term progestins should be carefully considered due to concerns over continuing bone formation in this age group. There is currently no consensus as to whether surgery should be avoided as much as possible to prevent multiple operations in the long term, or surgical treatment should be considered at an early stage before more severe lesions develop. Further research is required to determine which approach would offer a better long term outcome.